GAMBARAN STATUS KEBERSIHAN GIGI DAN MULUT PADA PEROKOK DI ASRAMA PUTRA BUMI GORA NTB YOGYAKARTA - Lu’lu’il Mahfuzoh; Susilarti Susilarti; Dwi Eni Purwati (Journal of Oral Health Care, 2017)
Oral health touches every aspect of our lives but is often taken for granted. Our mouth is a window into the health of our body. It can show signs of nutritional deficiencies or general infection. Systemic diseases, those that affect the entire body, may first become apparent because of mouth lesions or other oral problems. A lot of people may not realize if they had done a bad habit that worsen the oral health, one of them is smoking. It causes unpleasant breath odor, staining, tartar, and many more. The aim of this study was to determine oral hygiene status of the smokers in Asrama Putra Bumi Gora NTB Yogyakarta. This is a descriptive study with 30 responden include. Based on the research that has been done, oral hygiene status of the smokers at Asrama Putra Bumi Gora NTB Yogyakarta who has good criteria is about 53,3%, 46,7% of fair criteriaand no one has poor criteria. So the conclusion is most of the smokers at Asrama Putra Bumi Gora NTB Yogyakarta has good score of oral hygiene status.